FORMATION AND DEVELOPMENT OF THE PRODUCTION MECHANISM OF FLOUR AND GRAIN ENTERPRISES ON THE BASIS OF THE CLUSTER SYSTEM (World Economics and Finance Bulletin, 2022)
This article examines the formation and development of the production mechanism of flour and grain enterprises based on the cluster system
Keywords: Agar farmer and clusters, energy-saving flour; cluster and farmer; O’zdonmahsulot